Theoretical Analysis of the Iran and Israel Conflict: Identity, Power, and Ideology - Muhammad Usama Siddiqi; Brilliant Windy Khairunnisa (CV. FOUNDAE, 2025)
Israel's pre-emptive security measures, such as the destruction of Iranian nuclear facilities, Iran's nuclear ambitions, and its support for proxy groups like Hezbollah, have all contributed to the escalation of tensions over time. Both international security and regional stability have been significantly impacted by this conflict. This study aims to analyse how domestic political factors and systemic pressures influence foreign policy, especially in high-stakes disputes like Iran-Israel. It employs neoclassical realism and social constructivism theories to examine this complex issue, including the role of identity, power and ideology in it with qualitative exploratory research type by obtaining the data through literature, documents as well as focus group discussions. This study argues that the Iran-Israel rivalry is based on the interaction of ideational and material factors. Social constructivism sheds light on how ideological narratives fuel hostilities, while neoclassical realism reveals the systemic and domestic drivers of each state’s actions. Together, these viewpoints provide a comprehensive understanding of the conflict.